Real-time RT-PCR diagnostics of virus causing COVID-19 - E. V. Goncharova; A. E. Donnikov; V. V. Kadochnikova; S. A. Morozova; M. N. Boldyreva; I. S. Galkina; D. V. Blinov (IRBIS LLC, 2020)
Aim: the study was aimed to develop a reagent kit for the real-time RT-PCR diagnostics of virus causing COVID-19.Materials and Methods. Three target sites were chosen in the genome SARS-CoV-2. The testing included 220 samples, 48 artificially created positive samples (made from patients' biomaterial) and 172 clinical samples (scrapes from nasal and pharyngeal cavities, bronchoalveolar lavage, expectoration, endotracheal/nasopharyngeal aspirate, feces, post-mortem material), obtained from two medical centers. Preliminary, the obtained biomaterial was analyzed with a reagent kit of comparison. The evaluation was performed with a confidential interval CI 95%. The calculation of CI for the sensitivity and specificity was made based on the distribution of χ2.Results. The authors developed a technology of novel coronavirus infection (COVID-19) real-time RT-PCR diagnostics for the application in practical healthcare and proposed the variants of testing at all the stages (preanalytical, analytical, and post-analytical, including automated results processing). The proposed reagent kit meets the requirements of the World Health Organization and the Ministry of Healthcare of the Russian Federation. The study results demonstrated high sensitivity and specificity. The sensitivity was 100% (95% CI) 95.6-100%; the specificity was 100% (95% CI) 96.7-100%.Conclusion. The proposed reagent kit was registered in the RF as a medical product; the registration certificate No. RZN 2020/9948 dated 01.04.2020. The application of the reagent kit in network laboratories will provide patients with access to testing for the virus causing COVID-19 and contribute to quick differential diagnostics, improvement of pandemic control, and accurate statistics on the spread of the virus.